Financial Distress Prediction In Bank Muamalat Indonesia: Before And After Analysis of The Controlling Shareholder (PSP) Change - Septina Cicik Rohmawati; Rais Sani Muharrami (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2026)
A study aims to analyze and compare financial distress conditions, namely a decline in financial performance before bankruptcy, at Bank Muamalat Indonesia before and after the change of Controlling Shareholder (PSP) by BPKH. The analysis was conducted using the Zmijewski and Grover methods to identify differences in financial distress indicators between periods and compare the sensitivity of the two methods. This study uses a quantitative approach, drawing on secondary data from Bank Muamalat Indonesia's quarterly financial reports covering the period from the first quarter of 2018 to the second quarter of 2025. A normality test was conducted to select the testing method, and the Wilcoxon Signed Rank Test was used to assess the significance of differences between conditions before and after the change in PSP. The results show that, based on the Zmijewski method, indications of financial distress in the period after the PSP change were lower than in the previous period. Meanwhile, the Grover method consistently classified Bank Muamalat Indonesia as non-distressed both before and after the PSP change. These findings indicate differences in financial condition dynamics in the periods before and after the PSP.